Analysis of the quality of laboratory services on patient satisfaction and implications on hospital reputation - Sri Subekti; Sri Rochani Mulyani; Rukhiyat Syahidin (Sean Institute, 2024)
Research This study aims to analyze the relationship between the quality of laboratory services at RSUD Sepaku with customer satisfaction and its impact on hospital reputation. The population consisted of 192 users of laboratory services at RSUD Sepaku. The sample of 66 people was selected using the Slovin formula. Data were collected through questionnaires containing statements related to the research variables. Analysis analysis was carried out using path analysis, correlation coefficient, and coefficient of determination. determination. The results of the analysis show that the quality of laboratory services has a significant effect on patient satisfaction (significance: p<0.05, R square =5 1.9%). Patient satisfaction also has a significant effect on hospital reputation (significance: p<0.05, R square =7 3.4%). Service quality also directly has a significant effect on hospital reputation (significance: p<0.05, R square = 25.5%). Patient satisfaction acts as mediator variable between service quality and hospital reputation, with a larger greater indirect effect (61.7% > 25%). Together, service quality and patient satisfaction affect hospital reputation by 76.1%, while 23.9% is influenced by other variables. This research is expected to contribute to the Sepaku Hospital in improving the quality of laboratory services, improve patient satisfaction, and strengthen its reputation. The practical implications can help design more effective service strategies and improve the image of RSUD Sepaku in the local area.